Antimicrobial Susceptibility Patterns of Shigella Species among Children under Five Years of Age with Diarrhea in Selected Health Centers, Addis Ababa, Ethiopia - Basha Ayele; Zeleke Mekonnen; Tesfaye Sisay Tessema; Etsehiwot Adamu; Estifanos Tsige; Getenet Beyene (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Shigella and parasitic infections are common public health problems throughout the world. Shigellosis is an acute gastroenteritis infection and one of Ethiopia’s most common causes of morbidity and mortality, especially in children under five. High resistance rates to commonly used antibiotic agents have been documented in different locations in Ethiopia. Objective. This study aimed to characterize the antimicrobial features of the Shigella species isolated from children under five years of age with acute diarrhea in Addis Ababa, Ethiopia. Methods. Using a cross-sectional study, freshly passed fecal specimens were collected for intestinal parasite and bacterial isolation. Fecal samples for bacterial identification were placed immediately in Cary–Blair media and transported to the Ethiopian Public Health Institution (EPHI) laboratory. Antimicrobial susceptibility testing (AMST) was conducted using the disk diffusion method. Data were described using descriptive statistical tools. The association of independent and dependent variables was evaluated with logistic regression. A P value ≤0.05 was considered statistically significant. Results. The prevalence of intestinal parasites was 8.2% with seven different species. Among the 534 stool-cultured specimens, 47 (8.8%) were positive for Shigella species. Antimicrobial susceptibility testing (AMST) showed that 100%, 93.6%, 80.9%, 72.3%, and 57.5% were susceptible to norfloxacin, nalidixic acid, ciprofloxacin, gentamicin, and cefoxitin, respectively. However, 100% of the isolates were resistant to amoxicillin and erythromycin. More than 50% of the isolates were resistant to three and above antibiotics, while none of them were susceptible to all the antibiotics tested. All risk factors assessed did not show a statistically significant association with Shigella infection. Conclusion. The high levels of antibiotic resistance observed among the commonly prescribed antibiotics are alarming. The emerging resistance to ciprofloxacin and nalidixic acid signals a severe public health threat in the management of shigellosis. Raising awareness about resistance and educating health professionals, policymakers, and the public can help improve the quality of patient care and rational antibiotic use.